Women’s Autonomy Decision Making Power on Postpartum Modern Contraceptive Use and Associated Factors in North West Ethiopia - Samrawit Yonas Tadesse; Amanu Aragaw Emiru; Tadese Ejigu Tafere; Melash Belachew Asresie (Advances in Public Health)
Background. Most postpartum women (95%) do not want pregnancy within 24 months after birth, however, 70% of them do not use modern contraceptives. In Ethiopia postpartum modern contraceptive use is low. Evidences show that women’s autonomy within the household is the most important thing in modern contraceptive use. Yet, there is dearth of information in Ethiopian context. Therefore, this study was aimed to assess women’s autonomy on modern contraceptive use and its associated factors among women who attended their children immunization service. Methods. Facility-based cross-sectional study was carried out from May 5 to Jone15, 2017 in sekota town and its surroundings among 415 women who attended immunization service for their children. Participants were selected by using a systematic sampling technique. The data were collected through face-to-face interviews using pre-tested structured questionnaires. The data were entered into epi.info version7 and analyzed using SPSS version 23. Both descriptive and logistic regression analyses were performed. A P-value less than or equal to 0.05 at 95% confidence interval was set to test statistical significance. Result. The proportion of women’s decision making power on postpartum modern contraceptive use was 77.3%. Being counseled on postpartum family planning (2.29, 95% CI: 1.27, 5.71), discussed on postpartum family planning with their husbands (AOR = 14.62, 95% CI: 6.52, 32.75), and had the index child within one year after previous birth (AOR = 7.98, 95% CI: 2.52, 30.65) were found positively associated with women’s autonomous decision making power on postpartum modern contraceptive use. In addition, those women who knew that pregnancy could happen during the postpartum period (AOR = 6.53, 95% CI: 3.2, 14.12) were more autonomous in decision to use postpartum contraception. Conclusion. The proportion of women’s autonomous decision making power on postpartum modern contraceptive use was low. Those women who were counseled on postpartum family planning, discussed with partners, and those who knew that pregnancy could happen during the postpartum period had higher odds of autonomous decision making power. Therefore, strengthening counseling, educating on postpartum family planning, and encouraging women to discuss postpartum family planning with their husbands may improve women’s power.